2020
DOI: 10.20453/reh.v30i2.3760
|View full text |Cite
|
Sign up to set email alerts
|

Concordancia entre la radiografía panorámica y la tomografía computarizada de haz cónico en la relación de los terceros molares mandibulares con el conducto dentario inferior

Abstract: Objetivo: determinar la concordancia entre la radiografía panorámica y la tomografía computarizada de haz cónico en el análisis de la relación de los terceros molares mandibulares con el conducto dentario inferior en una población peruana. Material y métodos: la investigación fue observacional, descriptiva, transversal y retrospectiva. La muestra fue de 112 terceros molares y para la evaluación radiográfica se utilizó la clasificación modificada de Robert Langlais. Así mismo, otras variables fueron edad, sexo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…is frequency is similar to that described in other studies, such as the one by Maglione, et al (1) in Italy, who, when evaluating 133 third molars, found that 69.17 % were in intimate contact with the IAC. Likewise, Herrera Mujica, et al (7), when analyzing 112 mandibular third molars in CT scans, found 65.2 % in contact relationship. Another study by Kursun,et al (19) in Turkey, aer evaluating 180 third molars, found a contact relationship with the IAC of 57.8 % cases.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…is frequency is similar to that described in other studies, such as the one by Maglione, et al (1) in Italy, who, when evaluating 133 third molars, found that 69.17 % were in intimate contact with the IAC. Likewise, Herrera Mujica, et al (7), when analyzing 112 mandibular third molars in CT scans, found 65.2 % in contact relationship. Another study by Kursun,et al (19) in Turkey, aer evaluating 180 third molars, found a contact relationship with the IAC of 57.8 % cases.…”
Section: Discussionmentioning
confidence: 92%
“…It is used with keyboard and mouse on a desktop computer with a Windows 10 Pro® 64-bit operating system, Intel Core 2 duo® processor and a monitor with a minimum resolution of 1280 x 1024 pixels. e observation of the structures was conducted through visual inspection of the tomography in adequate conditions of physical space and ventilation, with dim ambient light and silence for interpretation (7). e imaging evaluation sessions were carried out in the morning hours, considering visual breaks from time to time working on the computer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 La tomografía computarizada de haz cónico tiene mayor claridad y nitidez, que la radiografía panorámica, en donde podemos ver estructuras anatómicas como la relación que hay entre el tercer molar y el conducto dentario. 44 complementario en el diagnóstico en endodoncia en donde se puede visualizar imágenes tridimensionales sumamente precisas y de alta calidad de la zona anatómica. A partir de ella se obtienen una serie de secciones bidimensionales de las estructuras irradiadas.…”
Section: Tomografía De Haz Cónicounclassified